E-Commerce in Southeast Asia: A Review of Developments, Challenges and Issues - Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2000)
This paper reviews the developments, challenges and issues in e-commerce in Southeast Asian countries. Given its implications for public policy, it focuses on e-commerce using the Internet. The review covers the developments in transaction values, the state of infrastructure (communication systems, payment systems, distribution and delivery systems), socioeconomic, cultural and legal environment and the regional and national initiatives. It also discusses the benefits and impacts as well as the emerging challenges and issues in e-commerce using the Internet. It then summarizes by identifying the main opportunities and challenges in e-commerce for countries in the region.
Keywords: 330; electronic commerce (e-commerce); information and communications technology (ICT); electronic government; Internet; Southeast Asia; E-Business; Informationstechnik; Internet; Südostasien